Recycled concrete waste as aggregate for concrete / Wan Ahmad Izzat Wan Abdullah, Hasni Suryani Mat Hasan - Wan Abdullah, Wan Ahmad Izzat; Mat Hasan, Hasni Suryani (2023)
In Malaysia, the awareness of product recycling, especially in the construction industry, is still low among people. The wastage of demolition processes is usually dumped into landfills when the demolition materials do not hold much value to be reused. This continuous effect will eventually fill the landfills with demolition wastes, particularly concrete materials. This phenomenon leads to several problems such as pest infestation, environmental damage, unpleasant sight, and health issue to the residents who live nearby the landfills. This study aims to develop an innovation to reuse demolition wastes into building materials. The research objectives are to identify the current issues relating to demolition waste materials, propose an innovation idea of recycling concrete waste from demolitions into new building materials, and explore the marketability potential of this demolition concrete waste.